Study on the mechanisms of action of berberine combined with fluconazole against fluconazole-resistant strains of Talaromyces marneffei - Kai-su, Pan; Hong, Luo; Dong-yan, Zheng; Yan-qing, Zheng; Andrianopoulos, Alex; Latgé, Jean-Paul; Cun-wei, Cao (Frontiers in Microbiology, 2022)
Talaromyces (Penicillium) marneffei (T. marneffei) is a thermally dimorphic fungus that can cause opportunistic systemic mycoses. Our previous study demonstrated that concomitant use of berberine (BBR) and fluconazole (FLC) showed a synergistic action against FLC-resistant T. marneffei (B4) in vitro. In this paper, we tried to figure out the antifungal mechanisms of BBR and FLC in T. marneffei FLC-resistant. In the microdilution test, the minimum inhibitory concentration (MIC) of FLC was 256 μg/ml before FLC and BBR combination, and was 8 μg/ml after combination, the partial inhibitory concentration index (FICI) of B4 was 0.28. After the treatments of BBR and FLC, the studies revealed that (i) increase reactive oxygen species (ROS), (ii) reduce ergosterol content, (iii) destroy the integrity of cell wall and membrane, (iv) decrease the expression of genes AtrF, MDR1, PMFCZ, and Cyp51B however ABC1 and MFS change are not obvious. These results confirmed that BBR has antifungal effect on T. marneffei, and the combination with FLC can restore the susceptibility of FLC-resistant strains to FLC, and the reduction of ergosterol content and the down-regulation of gene expression of AtrF, Mdr1, PMFCZ, and Cyp51B are the mechanisms of the antifungal effect after the combination, which provides a theoretical basis for the application of BBR in the treatment of Talaromycosis and opens up new ideas for treatment of Talaromycosis.